Narrativas digitais como espelhos para diferentes realidades locais na esfera rural escolar em Palmeira dos Índios: reconstruindo práticas de letramento com turmas do 8º ano do ensino fundamental - Barbosa, Luana de Farias (2018)
The present research, developed as a Master 's dissertation for the UFAL (PROFLETRAS / UFAL) Professional Master' s Degree Program in Literature, proposes to discuss different pedagogical practices of Portuguese - language literacy developed in two public schools in Palmeira dos Índios, Alagoas, in the context of rural scenery. My 8th grade students in Elementary School II are, mostly, formally or informally, farm workers, with an involvement in agriculture and livestock activities, the marketing of these products, and household chores, which are usually , in the urban environment, which is the responsibility of adults. The culture of the school institutions of which I am a part, in spite of its pedagogical proposal for all disciplines and especially for the Portuguese language, causes a deep disinterest in my students for learning, since, in addition to ignoring their (pre-) maturity in the sphere of work in the context of the field and, therefore, in the relations of production of everyday life, consider it in a deprecatory and inferior form. As a research problem, my main concern is the perception that my teaching practice in the classroom, fruit of both my education and the historical view of the school on language teaching, does not make sense for students in the field. The proposals do not reflect any traces of their reality, whether for their maintenance or to trigger processes of change. This research has the following questions: a) the search for a different pedagogy of Portuguese language teaching, from a different conception of literacy, could be an alternative to the research problem found, in the sense of being able to (re-) insert field students in school life? b) the use of technology, more specifically that of digital narratives, could collaborate with the process of developing the ability of written production as a social practice in the context of rural areas, so as to enable students to (re) construct different meanings for your local reality? The general objective of my dissertation was to develop a didactic proposal of reading and writing for the valorization and awareness of the local culture of the students participating in the 8th year of two schools of the municipal network of Alagoas, located in Palmeira dos Índios / AL and Igaci / AL, at light of a social perspective of literacy and an ethnographic approach to the school context. As a specific objective, I worked on written production activities articulated to the expressive resources of multiple languages, linked to different media (hypermedia). In both school contexts, the results obtained showed that the ideological approach of literacy allows the emergence of na approximation of students with the language, making them more users and not only foreigners in their own culture. The work with the multiletramentos, allowing and valuing the integration of multiple languages and cultures, opened space so that their local reality, materialized in the digital narratives, could be the scenario within which reflections on the language can occur.